PARTISIPASI PUBLIK DALAM PROGRAM BANTUAN LISTRIK PEDESAAN MASYARAKAT KABUPATEN MESUJI - Refly Setiawan (e-JKPP, 2017)
Public Participation is an effort to grow an independence and society’s empowerment in order to increase the quality of society as an element of good governance and to support the development. Participation consists of planning, implementing, evaluating, and pleasuring the result of development. The best form of participation isn’t only based on government view but also by the level of public participation in the development. Keywords : public participation, development